Optimizing the performance of photovoltaic cells IBC (contact back interdigitated) by numerical simulation - Nadjat Benadla; Kheireddine Ghaffour (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Solar energy is the most widely shared and abundant source all over the world. This kind of energy is exploited to produce electricity directly by the solar photovoltaic cell. Indeed, silicon  photovoltaic cells are the most widely spread technology. In the present article, we reported a numerical simulation of the interdigitated back contact (IBC) solar cell in order to obtain a higher conversion efficiency. The structure was realized on a p-type multi-crystalline silicon substrate, a p+ type amorphous silicon FSF, an n- type amorphous silicon based emitter, and a p- type BSF. The position of the emitter and the BSF were interdigitated and covered with ohmic contacts. The numerical simulation was carried out by SILVACO software under the Atlas module. The surface of structure was of a value of 10 cm2 under illumination AM1.5g. We studied the effect of the geometrical and the physical parameters of the structure with IBC on the performance of the cell. The optimum obtained conversion efficiency was 20.83%; this result confirms the potential of the heterojunction silicon technology.